Empowering Healthy Choices: The Dangers of Snacking Carelessly - Fernanda, Aprilia; Nisa', Ariqah Hidayatun; Assyaukani, Luthfi; Fadella, Risty; Ulilalbab, Arya; Prabowo, Nyono Dedi; Manik, Meintansari (Bhinneka Publishing, 2025)
The trend of unhealthy eating and the careless consumption of snacks among elementary school children remains a major nutritional issue in various countries worldwide, including Indonesia. Children tend to choose food based on their preferences. The shift in trends toward consuming snacks carelessly negatively affects children's nutritional status and health. This activity aimed to increase students’ knowledge and awareness about the importance of choosing healthy snacks and avoiding careless snacking habits. Nutrition education on snacking carelessly was the main emphasis of the community service programs. Thirty-sixth-grade students from SDN Bandar Lor II participated in the activity. PowerPoint and leaflets were used to communicate the content. The education session lasted for one hour. Pre- and post-tests were used to evaluate the results. The results of the activity showed that the participants engaged in the event in a participatory and active manner. The nutrition education on snacking carelessly effectively increased the students' knowledge by 4.6 points. Interactive methods, the use of infographic media, and hands-on practice enhanced participation and motivation in the children's learning process. Nutrition education on snacking carelessly effectively increased the students' knowledge.